On the sun-spiders of the ibirapemussu species-group of the genus Gaucha Mello-Leitão, 1924 (Solifugae, Mummuciidae), with description of a new species - Carvalho, Leonardo S.; Botero-Trujillo, Ricardo (Zootaxa, 2019)
A new solifuge species in the genus Gaucha Mello-Leitão, 1924 and the ibirapemussu species-group is herein described based on males and females collected at Itacuruba, State of Pernambuco, and Jaicós, State of Piauí, both in Northeastern Brazil. Males of the new species can be readily recognized by having the movable finger MM and MSM teeth reduced and of similar size. The present finding raises to twelve the number of described species in the genus, five of which belong to the ibirapemussu species-group. Besides, a new locality record for the species Gaucha ibirapemussu (Carvalho et al., 2010) is here presented, along with an updated identification key for all Gaucha species.